Mathematics learning during pandemic COVID-19 at Junior High School in Bukittinggi-Agam - Pipit Firmanti (Kaunia: Integration and Interconnection Islam and Science Journal, 2021)
The COVID-19 has become epidemic in the world at the end of 2019. It has impacted all sectors including education. The learning process that initially took place in the school has now been switched virtually. However, this worsens the students understanding in learning mathematics because previously they found it difficulties even in offline learning activities. Describing the learning proces during this pandemic condition is necesary and important to cope with this problem. The problems during this pandemic are related to three domains, namely cognitive, affective and psychomotor. Therefore, a research about this should be conducted. The method was qualitative research by interview and questionnaire. The participants were ten teachers and ten students from different junior high schools in Bukittinggi and Agam. From cognitive aspect, the result found that students could more easily understand the subject matter delivered by the teacher before the pandemic; the percentage of students' understanding of the material learning decreased by 10% during pandemic. From psycomotor aspect, teachers rarely use instructional media during the online learning process; The use of learning media also decreased by 60%, but the percentage of using online media as a learning resource increased by 50%. Moreover, the difficulty of using learning media for student increased by 40%. From affective aspect, teachers are more flexible in giving punishment to students who are not disciplined and educate students’ behaviors before pandemic than during the online learning process. Teacher gives punishment for students who were not disciplined decreased by 50% after virtual class. Overall, assessment done by teacher tends to the cognitive aspects during pandemic.